Construction of a Dual-Fluorescence Reporter System to Monitor the Dynamic Progression of Pluripotent Cell Differentiation - Wu-Sheng Sun; Ju-Lan Chun; Jeong-Tae Do; Dong-Hwan Kim; Jin-Seop Ahn; Min-Kyu Kim; In-Sul Hwang; Dae-Jin Kwon; Seong-Soo Hwang; Jeong-Woong Lee (Hindawi Limited, 2016)
Oct4 is a crucial germ line-specific transcription factor expressed in different pluripotent cells and downregulated in the process of differentiation. There are two conserved enhancers, called the distal enhancer (DE) and proximal enhancer (PE), in the 5' upstream regulatory sequences (URSs) of the mouse Oct4 gene, which were demonstrated to control Oct4 expression independently in embryonic stem cells (ESCs) and epiblast stem cells (EpiSCs). We analyzed the URSs of the pig Oct4 and identified two similar enhancers that were highly consistent with the mouse DE and PE. A dual-fluorescence reporter was later constructed by combining a DE-free-Oct4-promoter-driven EGFP reporter cassette with a PE-free-Oct4-promoter-driven mCherry reporter cassette. Then, it was tested in a mouse ESC-like cell line (F9) and a mouse EpiSC-like cell line (P19) before it is formally used for pig. As a result, a higher red fluorescence was observed in F9 cells, while green fluorescence was primarily detected in P19 cells. This fluorescence expression pattern in the two cell lines was consistent with that in the early naïve pluripotent state and late primed pluripotent state during differentiation of mouse ESCs. Hence, this reporter system will be a convenient tool for screening out ESC-like naïve pluripotent stem cells from other metastable state cells in a heterogenous population.